2014
DOI: 10.5860/crl12-426
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Database Design vs. Library Terminology Comprehension: Why Do Students Print Abstracts Instead of Full-Text Articles?

Abstract: When asked to print the full text of an article, many undergraduate college students print the abstract instead of the full text. This study seeks to determine the underlying cause(s) of this confusion. In this quantitative study, participants (n=40) performed five usability tasks to assess ease of use and usefulness of five commercial library databases and were surveyed on their understanding of library terminology. The study revealed that more than half of the students correctly defined the term "Abstract" a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, the students indicated that library language could be more accessible or user-friendly, thus reducing the need for explaining the meaning of a resource or service. After noticing hundreds of unclaimed printouts of article abstracts, Imler and Eichelberger (2014) narrowed their study to the meaning of abstract, a decidedly library term, and full-text, which is, arguably, a more accessible, user-friendly term. The authors found that 75% of the undergraduates surveyed could correctly identify the meaning of full-text (50% for the term abstract), but only 25% of the study participants could correctly retrieve the full-text of an article across several different databases, which suggested less of an issue with language and more so with database design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the students indicated that library language could be more accessible or user-friendly, thus reducing the need for explaining the meaning of a resource or service. After noticing hundreds of unclaimed printouts of article abstracts, Imler and Eichelberger (2014) narrowed their study to the meaning of abstract, a decidedly library term, and full-text, which is, arguably, a more accessible, user-friendly term. The authors found that 75% of the undergraduates surveyed could correctly identify the meaning of full-text (50% for the term abstract), but only 25% of the study participants could correctly retrieve the full-text of an article across several different databases, which suggested less of an issue with language and more so with database design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, as librarians became aware of usability research methods, they applied these techniques to test patron access to electronic resources. To note but a few examples from this ample literature: Cockrell and Jayne (2002) asked students to find eresources using library systems; Cummings and Johnson (2003) observed students using OpenURL linking; Wrubel (2007) offered a concise overview of e-resource usability testing; O'Neill (2009) considered how best to instruct patrons in OpenURL linking based on usability results; next generation catalogues (Majors, 2012) and discovery services (Asher, Duke, & Wilson, 2013;Fagan, Mandernach, Nelson, Paulo, & Saunders, 2012;Williams & Foster, 2011) have been studied thoroughly; Kress, Del Bosque and Ipri (2011) conducted a study to find out why students placed unnecessary ILL requests; and Imler and Eichelberger (2014) investigated how confusing vocabulary acts as a barrier to full-text. Considered as a whole, this usability research demonstrates librarians' awareness that the problems leading to full-text nonavailability are complex, arising from both library systems and human error.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bonnie Imler and Michelle Eichelberger analyzed students' research sessions to discern between "ease of use" and "usefulness" in library web page design, noting that the attractiveness of an easy-to-use search may "cause the researcher to lose sight of the …added value of library material over a simple Google search." 4 Students in the study printed abstracts rather than the full-text articles for two reasons. Either they were unable to locate the print function on the web page, or they were unclear on the meaning of the term abstract.…”
Section: Literature Reviewmentioning
confidence: 99%